Association of serum creatinine with aortic arch calcification in middle-aged and elderly adults: an observational cross-sectional study from China - Feifei Zhang; Nannan Hao; Lei Wang; Guoming Sun; Xiaoke Feng; Chunjian Li; Wenfeng Tan; Fang Wang (BMC Cardiovascular Disorders, 2022)
Abstract Background and aims Vascular calcification (VC) is a strong predictor of cardiovascular events and all-cause mortality in cardiovascular diseases (CVD). Renal dysfunction is closely related to VC. Serum creatinine, as an important indicator of renal function in chronic kidney disease (CKD), is closely associated with increased VC. Here, to explore the potential role of serum creatinine in CVD, we examined the association between serum creatinine level and aortic arch calcification (AAC) presence in a larger general population. Methods A total of 9067 participants aged > 45 years were included in this study. All participants underwent postero-anterior chest X-ray examination to diagnose AAC. According to the distribution characteristics, serum creatinine levels in male and female were divided into tertiles respectively. Univariate and multivariate logistic regression analysis were used to analyze the association between aortic calcification and serum creatinine. Results Participants included 3776 men and 5291 women, and 611 and 990 AAC were detected, respectively. Serum creatinine level in the female AAC group was significantly higher than that in the non-AAC group (p < 0.001), while there was no significant difference in male serum creatinine between the two groups (p = 0.241). After logistic regression analysis excluded confounding factors, with the first tertile of serum creatinine as the reference, multivariable-adjusted ORs and 95% CIs of the second and the highest tertile of female and male were 1.045 (0.856–1.276), 1.263 (1.036–1.539); 0.953 (0.761–1.193), 0.948 (0.741–1.198), respectively. Conclusion Elevated serum creatinine levels are independently associated with higher AAC incidence in female aged > 45 years old. Measuring serum creatinine levels may assist the early screening individuals at high risk of developing CVD. And higher attention should be given to female's serum creatinine levels in daily clinical practice.